Sistem Absensi Harian Antititip Menggunakan QR Code Berubah Otomatis dan Verifikasi Foto untuk SMP Negeri 204 Jakarta - Yuma Akbar; Mesra Betty Yel; Joey Abdiner Parlindungan Hutabarat; Muhamad Fawaz Kamali; Rekardius Tafonao (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2026)
Manual attendance management at SMP Negeri 204 Jakarta has proven to be inefficient and susceptible to data loss and damage. This study aims to develop and validate a QR Code-based attendance application called "E-SMART ABSENT" as a practical effort to support the digitalization of school administration. As part of a community service initiative within the educational sector, the application was developed using the Research and Development (R&D) method with a waterfall development model. The development stages included user needs analysis, system interface design, software coding using Kotlin and Node.js, and comprehensive system testing. Data were collected through field observations, interviews with relevant stakeholders, questionnaire distribution, and documentation. Product feasibility was measured using a Likert Scale ranging from 1 to 5. Validation results indicate that the application achieved a feasibility score of 86% from media experts, 96% from material experts, and 80% from Grade 7 homeroom teachers, all of which fall within the feasible to highly feasible categories. These findings suggest that the application is ready for broader implementation and has the potential to serve as a reference model for digital attendance system development in other schools.